Dialektika Relasional Transgender dengan Keluarga: Fenomenologi Transgender dalam Keluarga di Kabupaten Cianjur - Utami, Yessi Sri; Jamilah, Pupu; Ibrahim, Muhammad Taupiq (HK-Publishing, 2022)
AbstractThis study aims to examine the relationship between transgender and family in negotiating identity tendencies as transgender. The family is the smallest social group in society, has a vital role in the mental and physical development of each family member, and is also the group most affected by the clash of social norms related to gender construction. The results of this study indicate that transgender people negotiate their identity tendencies with verbal and non-verbal communication, occurring over a long period of time. The dialectical relationships that are established are not linear nor are they bound by space and time. However, the level of intimacy between transgender and family is linear, bound in units of space and time. The level of rejection and acceptance of gender identity will affect the level of intimacy in family relationships. Negotiating identity begins when the research subject experiences awareness of identity tendencies that are different from the social construction of gender. Forming a conceptual dialectic where conflicts that occurred in past relationships are dialectical elements that frame a relationship to be able to overcome subsequent conflicts.Keywords: relationship, transgender, family, dialectic, acceptanceÂ AbstrakPenelitian ini bertujuan menelaah hubungan transgender dengan keluarga dalam menegosiasikan kecenderungan identitas sebagai transgender. Keluarga merupakan kelompok sosial terkecil dalam masyarakat, mempunyai peranan vital dalam pekembangan mental dan fisik setiap anggota keluarga, juga merupakan kelompok yang paling terdampak oleh benturan norma sosial terkait konstruksi gender. Hasil dari penelitian ini menunjukan bahwa transgender menegosiasikan kecenderugan identitasnya dengan komunikasi verbal dan nonverbal, terjadi dalam kurun waktu yang panjang, Hubungan dialektika yang terjalin tidak bersifat linear juga tidak terikat pada ruang dan waktu. Namun tingkat keintiman hubungan transgender dengan keluarga bersifat linear, terikat dalam satuan ruang dan waktu. Tingkat penolakan dan penerimaan identitas gender akan berpengaruh terhadap tingkat keintiman dalam hubungan keuarga. Menegosiasikan identitas dimulai sejak subjek peneitian mengalami kesadaran terhadap kecenderungan identitas yang berlainan degan konstrksi sosial terhadap gender. Membentuk dialektika konseptual dimana konflik yang terjadi dalam hubungan dimasalalu merupakan elemen diaektika yang membinkai sebuah hubungan untuk dapat mengatasi konflik-konflik berikutnya.Kata kunci: hubungan, transgender, keluarga, dialektika, penerimaan